2022
DOI: 10.1039/d2gc03020a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of dihydroindazolo[2,3-f]phenanthridin-5(6H)-onesviaRh(iii)-catalyzed C–H activation of 2-aryl indazoles and annulation with iodonium ylides

Abstract: An efficient synthesis route of indazole fused dihydrophenanthridinones with excellent to almost quantitative yields under mild reaction conditions was developed by acid-controlled Rh(III)-catalyzed C-H activation of 3-arylindazoles and annulation with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Regrettably, the aliphatic iodonium ylides (2i-2m) did not proceed under standard conditions, which demonstrated that the transformation is sensitive to the size and nature of the dione compounds. 21 In order to gain deeper insight into the reaction mechanism, various control experiments were performed (Scheme 4). The hydrogen-deuterium exchange experiment of 1a with CH 3 COOD was conducted under standard conditions and the ortho-C(sp 2 )-H of the directing group was deuterated by 5% (Scheme 4a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regrettably, the aliphatic iodonium ylides (2i-2m) did not proceed under standard conditions, which demonstrated that the transformation is sensitive to the size and nature of the dione compounds. 21 In order to gain deeper insight into the reaction mechanism, various control experiments were performed (Scheme 4). The hydrogen-deuterium exchange experiment of 1a with CH 3 COOD was conducted under standard conditions and the ortho-C(sp 2 )-H of the directing group was deuterated by 5% (Scheme 4a).…”
mentioning
confidence: 99%
“…Regrettably, the aliphatic iodonium ylides ( 2i–2m ) did not proceed under standard conditions, which demonstrated that the transformation is sensitive to the size and nature of the dione compounds. 21…”
mentioning
confidence: 99%
“…However, the silver salt was not obviously influent on the proton transfer product (entry 15). Further investigation of the additive effect revealed that K 3 [Fe-(CN) 6 ] was the optimal choice, providing the annulated product 4 aa in 62% yield with excellent chemoselectivity (entries [16][17][18]. When the loading of K 3 [Fe-(CN) 6 ] was increased to 1.5 equiv., 4 aa could be afforded in 75% yield (entry 19).…”
Section: Resultsmentioning
confidence: 99%
“…[11] In 2020, Li and co-workers firstly reported a Rh(III)-catalyzed CÀ H activation/annulations of various arenes with HVIs for the synthesis of diverse cyclic skeletons. [12] Since then, various [4 + 2], [3 + 3] and [3 + 2] cyclization reactions of HVIs with different synthons in CÀ H functionalization have been established to access privileged skeletons by Maheswari, [13] Ji, [14] Kanchupalli, [15] Peng, [16] Hu [17] and other groups. [18] In these transformations, HVIs were employed as two-atom or three-atom synthons.…”
Section: Introductionmentioning
confidence: 99%